Advancements in Learning Content Management Systems (LCMSs): Shaping the Future of Digital English Language Education in Arabic Language Context A Case Study of Saudi Technical Colleges - Popoola Kareem Hamed; Ahmed Abdullah Alnaji Alqahtani (Ijaz Arabi Journal of Arabic Learning, 2026)
This study examines the impact of recent advancements in Learning Content Management Systems (LCMSs) on digital English language education at Saudi technical colleges. Using a mixed-methods research design, quantitative data were collected from 312 students and 48 English language instructors across five technical colleges, complemented by qualitative interviews. Statistical analysis revealed a significant improvement in students’ English language performance following LCMS integration, with mean achievement scores increasing from 63.4% to 78.9% (p < .01). Learner engagement indicators also showed notable growth, as 72% of students reported higher motivation levels and 68% demonstrated improved participation in online learning activities. From the instructors’ perspective, 81% reported enhanced efficiency in content development and assessment management, while LCMS analytics contributed to a 35% reduction in instructional planning time. Regression analysis further indicated that adaptive content delivery and multimedia integration were significant predictors of learning achievement (R² = .42). Despite these positive outcomes, the findings also highlight challenges, including varying levels of digital competency among faculty and infrastructure constraints reported by 29% of respondents. Overall, the study confirms that advancements in LCMSs play a transformative role in shaping learner-centered, data-driven English language education at Saudi technical colleges, while underscoring the need for sustained institutional support and professional development.